Pengaruh Punishment dan Penempatan Kerja terhadap Kinerja Pegawai pada Kantor Badan Pengelolaan Keuangan Pendapatan dan Aset Daerah Kabupaten Tapanuli Tengah - Juhari Mendrofa; Nelly A. Sinaga; Muhammad Iqbal Batubara (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to analyze the effect of punishment and job placement on employee performance at the Regional Financial, Revenue, and Asset Management Agency of Central Tapanuli Regency. The research method used is a quantitative approach with a correlational design. The population consists of 81 employees, and a saturated sampling technique was applied, meaning all population members were used as samples. Data were collected through questionnaires, observations, interviews, and documentation, and analyzed using multiple linear regression with SPSS. The results show that partially, punishment and job placement have a positive and significant effect on employee performance. Simultaneously, both variables also have a significant effect on employee performance with a significance value of < 0.05. The coefficient of determination (R²) value of 0.56 indicates that 56% of the variation in employee performance can be explained by punishment and job placement, while the remaining 44% is influenced by other factors outside the research model. Job placement has a more dominant effect compared to punishment. Therefore, fair and consistent implementation of punishment and appropriate job placement based on employee competence are important factors in improving employee performance.